2022
DOI: 10.1186/s12864-022-08745-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional responses are oriented towards different components of the rearing environment in two Drosophila sibling species

Abstract: Background The chance to compare patterns of differential gene expression in related ecologically distinct species can be particularly fruitful to investigate the genetics of adaptation and phenotypic plasticity. In this regard, a powerful technique such as RNA-Seq applied to ecologically amenable taxa allows to address issues that are not possible in classic model species. Here, we study gene expression profiles and larval performance of the cactophilic siblings Drosophila buzzatii and D. koep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…Although we have species with preferential use for Opuntia and for columnar cacti in both subgroups, D. koepferae and D. buzzatii are adapted to different hosts for a longer time than those of the mulleri complex studied here. In addition, a preliminary study demonstrated that D. buzzatii have a high divergence on larvae gene expression compared to D. koepferae (40), reinforcing the variance that we have observed. In mulleri complex, although not high, it is noteworthy that the subclusters of gene expression from D. m. mojavensis, D. m. baja, D. m. sonorensis, and the subcluster from D. arizonae and D. m. wrigleyi.…”
Section: Gene Expression In Larvae Is One Of the Factors Shaping The ...supporting
confidence: 83%
See 3 more Smart Citations
“…Although we have species with preferential use for Opuntia and for columnar cacti in both subgroups, D. koepferae and D. buzzatii are adapted to different hosts for a longer time than those of the mulleri complex studied here. In addition, a preliminary study demonstrated that D. buzzatii have a high divergence on larvae gene expression compared to D. koepferae (40), reinforcing the variance that we have observed. In mulleri complex, although not high, it is noteworthy that the subclusters of gene expression from D. m. mojavensis, D. m. baja, D. m. sonorensis, and the subcluster from D. arizonae and D. m. wrigleyi.…”
Section: Gene Expression In Larvae Is One Of the Factors Shaping The ...supporting
confidence: 83%
“…The resolution of gene annotation for D. arizonae was similar to D. mojavensis subspecies due to the recent (1.5 Mya) divergence between them (43), whereas for D. buzzatii and D. koepferae it was ~23% smaller compared to D. mojavensis, as expected since they are more distant related species (44). Similar amount of genes had been annotated previously in the D. buzzatii (45,46) and D. koepferae (46,40) genomes. Since analysis on HLAU genes is the focus of this study, their efficient annotation is relevant.…”
Section: Genome Assemblies and Gene Annotationsupporting
confidence: 73%
See 2 more Smart Citations